Factors Affecting Peer-to-Peer (P2P) Lending Bad Debts in Java and Sumatra - Zuni Nur Khasanah; Hasan Al-Banna (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to analyse the factors that influence bad debts in Peer-to-Peer (P2P) lending platforms in Jawa and Sumatra. The emergence of fintech as an alternative financing solution for the public and UMKM has created new challenges in the form of high credit risk. This study is motivated by the rapid growth of the fintech industry in Indonesia and the limited academic studies comparing credit risk based on geographical region. Methodology: This study uses monthly time series secondary data for the period January 2021 – December 2024 obtained from the OJK Fintech Lending Statistics report. This study uses the Autoregressive Distributed Lag (ARDL) method to see the short-term and long-term effects of the variables of loan amount, loan purpose (individual and business entity), and male and female debtors. Findings: The results showed that the amount of the loan did not have a significant effect on bad debts. Meanwhile, other variables have a significant effect on bad debts. Novelty: This research has novelty in terms of region; the research focuses on two regions in Indonesia, namely Jawa and Sumatra. These two regions were chosen because they have different economic characteristics of infrastructure and access to financial services.